Horace Greeley's New-York tribune : Civil War-era socialism and the crisis of free labor - Tuchinsky, Adam-Max (Cornell University Press, 2009)
From the Publisher: In the mid-nineteenth century, Horace Greeley's New-York Tribune had the largest national circulation of any newspaper in the United States. Its contributors included many of the leading minds of the period-Margaret Fuller, Henry James Sr., Charles Dana, and Karl Marx. The Tribune was also a locus of social democratic thought that closely matched the ideology of Greeley, its founder and editor, who was a noted figure in politics and reform movements. Adam Tuchinsky's book recalls an earlier style of opinion media, with "participant editors" acting not unlike today's Internet journalists-professionals and amateurs alike-who digest the news and also shape it. It will appeal to all readers interested in the history of the media and its relationship to partisan politics. During its Greeley era, the Tribune was simultaneously an influential voice in the Whig and Republican parties and a vigorous advocate of socialism. Historians and biographers have struggled to reconcile these seemingly contradictory tendencies. Tuchinsky's history of the Tribune, by placing the newspaper and its ideology squarely within the political, economic, and intellectual climate of Civil War-era America, illustrates the connection between socialist reform and mainstream political thought. It was democratic socialism-favoring free labor, and bridging the divide between individualism and collectivism-that allowed Greeley's Tribune to forge a coalition of such disparate elements as the old Whigs, new Free Soil men, labor, and staunch abolitionists. This progressive coalition helped ensure the political success of the Republican Party. Indeed, even in 1860, proslavery ideologue George Fitzhugh referred to socialism as greeley's "lost book"--The overlooked but crucial source of the Tribune's and, by extension, the Republican Party's antagonism toward slavery and its more general free labor ideology. Tuchinsky brings forth this lost history and demonstrates that, amid the sectional crisis and the battle over slavery, Greeley and the Tribune promoted a viable form of democratic socialism that formed one foundation of modern liberalism in America